Sterilisation effect study on granular hydroxyapatite (HA) - Saidu, Mohd Fharid; Masri, Mashita; Khalid, Khadijah; Fazan, Fazilah; Khalid, Kamarul Ariffin (Malaysian Medical Association, 2004)
Hydroxyapatite is a calcium phosphate bioceramic that has been shown by many authors to be biocompatible with bioactive properties. It is widely accepted as the best synthetic material available for surgical use as a bone graft substitute. HA granules produced by AMREC-SIRIM from local materials underwent 5 types of sterilisation techniques with different ageing periods. Samples were tested for chemical and phase composition and microbial contamination before and after being sterilised. From the microbiological tests done, none of the unsterilised positive control yielded a positive culture. Results from X-Ray diffraction studies found that all the sterilisation techniques did not chemically degrade or structurally change the HA granules significantly.